Statistical properties of the least squares estimator of maximum excreted drug amount - Prodanova, Krasimira (Ann. Sofia Univ. Fac. Math. and Inf., 1996)
Inaccuracy in estimation of the maximum excreted drug amount (U^∞) is the main cause of errors in determination of some pharmacokinetic parameters of drugs. Usually, one estimates U^∞ using observed values of the cummulative excretion (U(t)). This paper uses a new stochastic model to obtain the least squares estimator of U^∞. The advantages of the model are that it is applicable for any drug, whose pharmacokinetics may be formalized with a linear n-compartment model (n=1,2,3,...) with or without phase of absorption and it may be used when the measurements for U(t) are non-equidistant.